The Role of Family Education in Forming Children's Morals in Adiwarno Village, Batanghari District, East Lampung Regency - Nur Aini; Siti Roudhatul Jannah; M. Kharis Fadillah (Journal of Research in Islamic Education, 2024)
Children are a gift that has been given by Allah Swt to every family, with the presence of a child in the midst of the family adds happiness to every parent, with the presence of a child all parents definitely want their children to become pious children, to create all that parents should provide appropriate education to their children at their age of development. Because the first and foremost education obtained by a child is from family education. The importance of education in this family means that every parent should be able to understand what kind of education should be taught to children so that they can form good morals, which can produce a pious and pious generation. However, there are still parents who do not care about their children, both in terms of attitude and speech. This study is a descriptive qualitative study, the subjects of the study were children aged 7-12 years, while the informants of this study were parents, children and neighbors or people who were considered to know about the child's personality. The methods used in this study were observation, interviews and documentation. To check the validity of the data using data triangulation. After conducting research on family education in the formation of children's morals in Adiwarno Village, Batanghari District, East Lampung Regency, namely by providing examples, advice and understanding, direction, and habituation. And the teachings given about morals are religious education, such as providing learning about monotheism, politeness, speech, instilling good things in children. When educating, parents prioritize affection so that children can accept the teachings given to them.